Hubungan Paritas Dan Persepsi Ibu Hamil Dengan Hiperemis Gravidarum Di Rumah Sakit Umum Daerah Kabupaten Majene Tahun 2023 - Arfiani Busman; Resky Devi Akib; Wahida Munir (LPPM STIKES Marendeng Majene, 2023)
Objective: In general, the aim of this study was to determine the relationship between parity and maternal perceptions of hyperemia gravidarum at the Majene District General Hospital. Methods: This type of research is a quantitative study using a cross-sectional design. The population in this study were all pregnant women. The sampling technique uses the Total Sampling technique. The sample of this research is 47 people. The analysis was carried out with the help of the SPSS 22.0 application. The test was carried out by observing the significance value of the Chi Square test. Results: The results of the chi-square test on the pregnant parity variable were obtained with a value of p = 0.016 <0.05. The results of the chi-square test on the perception of pregnant women were obtained with a value of p = 0.211> 0.05. Conclusion: In the parity variable of pregnant women there is a relationship between parity of pregnant women and the incidence of hyperemesis gravidarum and in the perception variable of pregnant women there is no relationship between the perception of pregnant women and the incidence of hyperemesis gravidarum